Investigation of the effect of magnet thickness on output power and torque of PM BLDC machines using parametric approach method - Topaloğlu, İsmai̇l; Ocak, Cemi̇l; Bayindir, Ramazan (IEEE, 2011)
The main purpose of this paper is to describe the effect of magnet thickness on output power and torque of a 500 Watts PM BLDC motor using parametric approach method to reduce the amount of magnet material. Because the cost of magnet material is high compared with the cost of the other materials used in electric motors, required amount of magnet material are important considerations in motor selection. In the approach, the motor specifications, numerical optimization technique and solution method are effectively introduced. Additionally, the proposed approach provides the effective information to electrical machine designers. Finally, effects of magnet thickness to output parameters simulated and graphically represented. The proposed machine has 24 slot, 4 pole (surface mounted) and inner runner configuration.
Keywords: 7. Clean energy